Preventing Foodborne Illness: Clostridium botulinum - Keith R. Schneider; Mickey E. Parish; Renée M. Goodrich; Taylor Cookingham (EDIS)
Botulism is caused by the nerve toxins produced by the bacterium Clostridium botulinum, often resulting in a serious paralytic condition that can lead to death. This document is FSHN04-06, one of a series of the Food Science and Human Nutrition Department discussing common foodborne pathogens of interest to food handlers, processors, and retailers; Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Date Published: November 2004.